Digital Divide among the Faculty Members of Dental Prosthetics Departments in Dental Schools of Medical Universities in Tehran in 2014 - Javad Ghazimirsaeid; Hoseain Dehdari; Fatemeh Sheikhshoaei (Islamic Dental Association of Iran, 2015)
Background and Aim: Advances in information and communication technology (ICT) have had a great impact on people's lives. Beside all the benefits, they have caused some problems such as digital divide. This study aimed to assess digital divide among the faculty members of dental prosthetics departments in dental schools of medical universities in Tehran in 2014. Materials and Methods: This applied research had a descriptive analytical design and was conducted through a survey analysis. The statistical population of this study consisted of all the faculty members of dental prosthetics departments in dental schools of medical universities in Tehran (n=100). Data were collected using a researcher-designed questionnaire; its validity was confirmed by an expert panel and its reliability (α=0.978) was confirmed using Cronbach's alpha test. The data were analyzed using SPSS version 16and t-test, ANOVA, Chi-square test and the Pearson's correlation test. Results: A total of 82 questionnaires were filled out and returned by the faculty members. The results showed that 97.5% of the study population had access to computers at home and at work; 96.3% had Internet access at home and 97.5% had access to Internet at work; 51.9% (n=42) of the faculty members used these technologies several times a day; 29.6% (highest frequency) reported average daily use of these technologies to be half an hour to an hour. Marital status and academic ranking had significant effects on the skills of using ICT. Age and years of instruction were also effective on ICT literacy, the ability and skills to use ICT and the requirements to use ICT. Conclusion: Based on the results, marital status, academic ranking, age and years of instruction are effective in use of ICT by the faculty members.